Effect of a processing delay between direct and delayed sound in simulated open fit hearing aids on speech intelligibility in noise - Roth, Sebastian; Müller, Franz-Ullrich; Angermeier, Julian; Hemmert, Werner; Zirn, Stefan (Frontiers in Neuroscience, 2024)
Subjects with mild to moderate hearing loss today often receive hearing aids (HA) with open-fitting (OF). In OF, direct sound reaches the eardrums with minimal damping. Due to the required processing delay in digital HA, the amplified HA sound follows some milliseconds later. This process occurs in both ears symmetrically in bilateral HA provision and is likely to have no or minor detrimental effect on binaural hearing. However, the delayed and amplified sound are only present in one ear in cases of unilateral hearing loss provided with one HA. This processing alters interaural timing differences in the resulting ear signals. In the present study, an experiment with normalhearing subjects to investigate speech intelligibility in noise with direct and delayed sound was performed to mimic unilateral and bilateral HA provision with OF. The outcomes reveal that these delays affect speech reception thresholds (SRT) in the unilateral OF simulation when presenting speech and noise from different spatial directions. A significant decrease in the median SRT from -18.1 to -14.7 dB SNR is observed when typical HA processing delays are applied. On the other hand, SRT was independent of the delay between direct and delayed sound in the bilateral OF simulation. The significant effect emphasizes the development of rapid processing algorithms for unilateral HA provision.